Family Planning Counseling and Safari (IUD and Implant) : Penyuluhan dan Safari Keluarga Berencana (IUD dan Implant) - Ni Made Rosiyana; Enggar Enggar; Yuni Kristiani Tumani; Margareta Paula Klara (Poltekkes Kemenkes Palu, 2022)
Introduction: A well-implemented family planning program can prevent maternal death through the use of contraception. The use of long-term contraceptives such as IUDs and implants is considered much more effective in reducing birth rates, but their use is still very low. The purpose of this community service is expected to be able to open insight and foster interest in fertile age couples (PUS) in making decisions to join in the use of long-term contraceptives, especially IUDs and implants. The method used is counseling to WUS and PUS who are domiciled in Loru Village, Sigi Biromaru District about IUDs and implants. The number of EFA targets in counseling was 28 people, which was then carried out on a family planning safari for counseling participants who decided to use an IUD or implant contraceptive device. The result of this community service activity is a change in attitude in choosing contraceptives after counseling, marked by 6 people deciding to use long-term IUD contraception and 9 other people deciding to use implant contraceptives. The need for contraceptive counseling that involves husbands and families, so that there are no obstacles in decision making by mothers.